Makna Pencatatan Perkawinan pada Peraturan Perundang-undangan ditinjau dalam Hukum Islam - Anto, Adrianto (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This research is motivated by invalidity unregistered marriage based on Positive law and Islamic law. In Islamic law marriage registration is condicio sine quanon is istinbath of Islamic law. Marriages that are not registered according to the regulations of Islamic law for condicio sine quanon for marriage registration be a contradictory matter what happens in practice wedding in the middle of public. This study aims to determine The mean a recording of marriage In istinbath of islamic law and want to know in mean of recording of marriage in islamic law And want to know the mean of recording of marriage in an effort to realize goals Maslahah which is on public. This research uses qualitative approach with library research. The research results show abouth the recording of marriage is condicio sine quanon in istinbath of Islamic law and meaning of recording of marriage in Islamic law is is as evidence next to the witnes. The mean of recording of marriage in an effort to realize goals Maslahah which is on public as Maslahah Daruriyyah like a guard that must be maintained Is ad-Din, an-Nafs, al-‘Aql, an-Nasab wa al-Mal.